2019
DOI: 10.3847/1538-4357/ab08e5
|View full text |Cite
|
Sign up to set email alerts
|

Unresolved Binaries and Galactic Clusters’ Mass Estimates

Abstract: Binary stars are present in all stellar systems, yet their role is far from being fully understood. We investigate the effect of unresolved binaries in the derivation of open clusters' mass by star counts. We start from the luminosity functions of five open clusters: IC 2714, NGC 1912, NGC 2099. Luminosity functions are obtained via star counts extracted from the 2MASS database. The fraction of binaries is considered to be independent on stellar magnitude. We take into account different assumptions for the bin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 39 publications
2
31
1
Order By: Relevance
“…Therefore, binaries are ideal tracers for investigating the formation and evolution of OCs, as well as the dependence on their forming locations and environments. Furthermore, binary stars are essential in determining the total mass (Borodina et al 2019) and the stellar mass function (Kroupa & Boily 2002) of OCs.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, binaries are ideal tracers for investigating the formation and evolution of OCs, as well as the dependence on their forming locations and environments. Furthermore, binary stars are essential in determining the total mass (Borodina et al 2019) and the stellar mass function (Kroupa & Boily 2002) of OCs.…”
Section: Introductionmentioning
confidence: 99%
“…η = 0.3) is expected (see e.g. Gizis & Reid 1995;Bouvier et al 2001;Böhm-Vitense 2007;Boudreault et al 2010;Khalaj & Baumgardt 2013;Sheikhi et al 2016;Borodina et al 2019;Li et al 2020) even if the distribution of η can be quite large, ranging from about 30% to 70% (Sollima et al 2010). Moreover, the value of η = 0.3 we adopted is fully suitable for clusters Praesepe (e.g.…”
Section: Towards a Practical Applications In The Gaia Eramentioning
confidence: 86%
“…The evolution of stars in close binary systems leads to the formation of 'exotic' stars: blue straggler stars, cataclysmic variable stars and so forth (Hurley et al 2001;Carraro & Seleznev 2011;Hong et al 2017). Finally, one needs to take unresolved binary and multiple stars into full account when obtaining photometric estimates of open cluster masses (Borodina et al 2019;Rastello et al 2020;Borodina et al 2021) or spectroscopic estimates of their dynamical mass (Seleznev et al 2017;Rastello et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, Li et al (2017) had found α = 0.6 − 0.8 for NGC6362, NGC6652, and NGC6838. In open clusters the binary ratio is α 0.3 (see Borodina et al (2019) for a review, and Niu et al (2020)). The binary ratio for the field stars seems to be even larger (see Duchêne & Kraus (2013) for a review).…”
Section: Introductionmentioning
confidence: 99%